Nuove tendenze nel cinema postbellico dell'ex Jugoslavia - Borjan, Etami (Array, 2011)
The chapter analyzes the main tendencies in the film production of the new postwar Yugoslav cinemas in the last two decades and discusses the problems related to the actual position of these cinemas within European context. Although the article outlines briefly the main tendencies in all the countries of the former Yugoslavia, it focuses mainly on the recent postwar film production of three countries: Croatia, Serbia and Bosnia and Herzegovina. Cinema, together with mass media, is a tool for the production of culture but it also represents the dynamics of a particular culture. Through the analysis of the main tendencies in the new cinemas the paper investigates to what extent the filmic text shapes the mechanisms of discursive formations of new national identities.